Sociology in Medical Undergraduate Education: A Survey in Greece - Pelagia Soultatou; Trisevgeni Trantali; Constantinos-Chrysovalantis Patithras; Charalampos Economou (International Medical Education)
The integration of sociology into medical education is essential for cultivating a nuanced understanding of the complex interplay between social determinants and health outcomes. This national cross-sectional survey utilized a qualitative, descriptive research approach to examine the inclusion of sociology as a course in the undergraduate curricula of medical schools in Greek higher education. Data collection and analysis were conducted through a comprehensive review of the syllabi from all seven medical schools in Greece. The analysis revealed that none of the seven undergraduate medical curricula include sociology as a discrete course. Social medicine is offered as a discrete course in three out of the seven programs, whereas sociological concepts are present in the majority of the medical curricula (six out of seven). A significant gap in the integration of sociology as a discrete course within Greek medical graduate education is revealed. To better equip future medical doctors with sociological lenses towards medical practice, a more comprehensive integration of sociology into medical training is recommended.